Correcting a misidentification: Expanding the known range of the rare desmid Gonatozygon dicranoaculeatum (Zygnematophyceae, Gonatozygaceae) to India and the Asian continent - Vuuren, Sanet Janse Van; Levanets, Anatoliy (Phytotaxa, 2025)
N/A